'Paying our own way': Application of the capability approach to explore older people's experiences of self-funding social care. (May 2018) - Tanner, Denise; Ward, Lizzie; Ray, Mo
Adult social care policy in England is premised on the concept of personalisation that purports to place individuals in control of the services they receive through market-based mechanisms of support, such as direct payments and personal budgets. However, the demographic context of an ageing population and the economic and political context of austerity have endorsed further rationing of resources. Increasing numbers of people now pay for their own social care because either they do not meet tight eligibility criteria for access to services and/or their financial means place them above the threshold for local authority-funded care. The majority of self-funders are older people. Older people with complex and changing needs are particularly likely to experience difficulties in fulfilling the role of informed, proactive and skilled navigators of the care market. Based on individual interviews with older people funding their own care, this article uses a relational-political interpretation (Deneulin, 2011) of the capability approach (CA) to analyse shortfalls between the policy rhetoric of choice and control and the lived experience of self-funding. Whilst CA, like personalisation, is seen as reflecting neo-liberal values, we argue that, in its relational-political form, it has the potential to expose the fallacious assumptions on which self-funding policies are founded and to offer a more nuanced understanding of older people's experiences.